MarathOn Multiscreen: group television watching and interaction in a viewing ecology - Anstead, Edward; Benford, Steve; Houghton, Robert (2016)
This paper reports and discusses the findings of an exploratory study into collaborative user practice with a multiscreen television application. MarathOn Multiscreen allows users to view, share and curate amateur and professional video footage of a community marathon event. Our investigations focused on collaborative sharing practices across different viewing activities and devices, the roles taken by different devices in a viewing ecology, and observations on how users consume professional and amateur content. Our Work uncovers significant differences in user behaviour and collaboration when engaged in more participatory viewing activities, such as sorting and ranking footage, which has implications for awareness of other users’ interactions while viewing together and alone. In addition, user appreciation and use of amateur video content is dependent not only on quality and activity but their personal involvement in the contents.